Conservative therapy of patients with pneumoempyema in the postoperative period - V. Komarchuk; D. Lopatenko (Kazimierz Wielki University, 2017)
It was сonducted discriminant analysis that allowed a to make discriminant equation for determination the probability of fatal resalt in the treatment patients with pneumoempyema; this research based on data changes of interleukin 6, 8, 10 level. It was considered the features of post-operative treatment of patients with pneumoempyema using our method. It was analyzed and compared amount of  mortality.